Effectiveness of Spinach Extract Administration on Hemoglobin Level Improvement in Pregnant Women with Mild Anemia at Wiritasi Health Center - Husnaini Husnaini; Retno Dewi Prisusanti (PPNI UNIMMAN, 2025)
Mild anemia in pregnant women remains a common health problem at the primary healthcare level and may negatively affect both maternal health and fetal development. One non-pharmacological approach to managing anemia is the utilization of local food sources rich in iron, such as spinach. This study aimed to determine the effectiveness of spinach extract in increasing hemoglobin levels among pregnant women with mild anemia at Poskesdes Wiritasi. This study employed a quasi-experimental design using a one-group pretest–posttest approach without a control group. The sample consisted of 30 pregnant women diagnosed with mild anemia who were selected through purposive sampling. The intervention involved the regular administration of spinach extract for 14 consecutive days. Hemoglobin levels were measured before and after the intervention using a standard hemoglobin testing device. Data were analyzed to assess differences in hemoglobin levels before and after the intervention. The results showed a significant increase in hemoglobin levels following the administration of spinach extract. These findings indicate that spinach extract has a positive effect on improving hemoglobin levels in pregnant women with mild anemia. Therefore, spinach extract may serve as an effective, safe, and easily applicable local food–based nutritional intervention for the prevention and management of mild anemia among pregnant women at the village healthcare level.